Exploring the Effectiveness of End-to-End Testing Frameworks in Modern Web Development - Talakola, Swetha (International Journal of Emerging Research in Engineering and Technology, 2022)
Dependability and quality of software constitute first issues in contemporary web development. Traditional testing approaches cannot find integration problems among multiple components as web systems get ever more complicated. Since end-to- end (E2E) testing tools help developers replicate real-world user interactions and validate the complete running performance of an application, they are becoming more and more crucial. The need of E2E testing in improving software dependability is investigated in this work. It underlines the main benefits of early defect discovery, enhanced user experience assurance, and thorough E2E testing system coverage of improvements. Furthermore included are issues that could undermine the effectiveness of automated testing systems: test flakiness, high maintenance overhead, and extended running times. Examining important E2E testing systems including Cypress, Selenium, and Playwright, this paper offers a thorough assessment based on their strengths, weaknesses, and fit for various project objectives. Modern DevOps systems first concentrate on analyzing important components including simplicity of use, performance, debugging tools, and interface. Furthermore, best practices for executing E2E testing include CI/CD pipeline integration, test case design optimization, and artificial intelligence-powered automation applied to raise test dependability. A real case study using an E2E testing infrastructure shows how a large financial company improved test stability and deployment efficiency. This study investigates emerging E2E testing trends including low-code/no-code testing solutions, cloud-based testing, and artificial intelligence-driven automation and so influences the course of software quality assurance. The results emphasize the need of applying scalable, efficient, sustainable E2E testing techniques to guarantee strong and remarkable online applications in a development environment running ever quicker